Wind power energy and cost analysis study in Turkey - Guneri, A. F. (MANEY PUBLISHING, 2008)
Energy is a vital input for the social and economic development of any nation. With increasing agricultural and industrial activities in Turkey, the demand for energy is also increasing. Energy should be supplied in several ways, but the important thing is how energy can be supplied cost effectively. Wind has been proven as a reliable and cost effective energy source. Technological improvements have placed wind energy in a position that competes with conventional power generation technologies. The current interest in wind energy is based on the need to develop clean, sustainable energy systems that can be relied on in the long term future. Modern aerodynamics and engineering have improved wind turbines to the extent that they now provide reliable, cost effective, pollution free energy for individual, community and national applications. The significant benefits of wind power should play an increasingly important role in decisions about future power plant construction. The purpose of this paper is to both describe the characteristics of wind power energy, and to analyse its actual cost, using the data provided by a wind turbine in Turkey.
Keywords: Energy; Wind energy; Cost analysis; FEASIBILITY; Energy & Fuels